Peranan Musyawarah Guru Mata Pelajaran (MGMP) Sebagai Organisasi Pembelajar terhadap Peningkatan Kompetensi Guru Bidang Studi - Ambarita, Erika; Meilani, Yohana F. Cahya Palupi; Wanasida, Albert Surya (SUKMA: Jurnal Pendidikan, 2022)
The teacher community in an educational unit is needed by teachers, because it is a place for learning to organize in teaching materials and improving the quality of teaching carried out in the classroom which automatically has an impact on increasing the compe- tence of the teachers themselves. Sharing information about the latest things in the world of education will increase the knowledge of teachers in this group of organizations. This study aims to obtain information about the role of the Subject Teacher Consultation (MGMP) in improving the competence of teachers in the field of English studies in the teaching and learning process in the classroom. This study is a descriptive analysis of the number of English teachers in the West Jakarta I MGMP as many as 133 people who are the pop- ulation in this study. Sampling using random sampling technique so that the number of samples obtained as many as 54 teachers. Primary data is used in this study, which means that data are obtained directly from the respondents. The results of the study for data analysis used the average formula (mean). The research instru- ment used a Likert scale. The results showed that with the involvement of teachers as members of the English Subject Teacher Consultation community, it was very useful  to  improve  the  competence  of  teaching  English in the classroom, with the aim that students could un- derstand and master the teaching material presented by the teacher.